The Influence of Live Streaming and Short Video Marketing on TikTok on Purchase Intention in Generation Z - Sarifuddin T; Cahyaning Raheni; Ulfa Cahyaning Kasih (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In the era of accelerated digital transformation, TikTok has emerged as a formidable platform shaping consumer behavior via interactive and visually compelling content, rendering an assessment of its marketing efficacy imperative. This study examines the impact of live streaming and short video marketing on the purchase intention of Generation Z, specifically within the cosmetics and skincare industry. Utilizing a quantitative method with an explanatory research design, empirical data were gathered from 120 Generation Z participants through an online survey administered via non-probability accidental sampling. The dataset was evaluated utilizing multiple linear regression analysis, validated by classical assumption testing encompassing normality, multicollinearity, and heteroscedasticity. The empirical results demonstrate that live streaming and short video marketing exert a positive, statistically significant effect on purchase intention, both independently and concurrently, with live streaming exhibiting the predominant influence. A coefficient of determination of 0.809 indicates that these independent variables account for 80.9% of the total variance in consumer purchase intention. Consequently, this study suggests that enterprises must strategically leverage interactive digital media to bolster engagement and stimulate purchase decisions, concluding that integrated social media approaches are vital for successfully capturing the contemporary Generation Z demographic